Appropriateness of Acetaminophen Dosing by Caregivers of Pediatric Patients Presenting to the Emergency Department at the University Pediatric Hospital in Puerto Rico - Vélez-Rivera, Suzette M.; Rodríguez-Rodríguez, Nashicel J.; Ortiz-Vera, Yakelin A.; Parambil, Ashley; Hernández-Muñoz, José J. (Puerto Rico Health Sciences Journal, 2021)
Objective: Evaluate the appropriateness of acetaminophen dosing by caregivers seeking care for their children/wards at the emergency department of a pediatric hospital. Methods: Design: Cross-sectional descriptive study. Setting: The emergency department of the University Pediatric Hospital in San Juan, Puerto Rico. Participants: Eighty-eight caregivers who had, in the past 24 hours, administered a known quantity of acetaminophen to a pediatric patient under their care and were visiting the emergency room with that patient. Intervention: The caregivers were interviewed by the investigators, using a standardized questionnaire. Main outcome measures: The appropriateness of the acetaminophen doses administered by caregivers. The product’s dosage form and strength, measurement device used (if any), and demographic data (of the caregiver and child) were also collected. Doses of 10 to 15 mg/kg of acetaminophen were considered appropriate. Results: Overall, 45% of the caregivers had administered an inappropriate dose. Of these, 70% were subtherapeutic and 30% were supratherapeutic. Although 74% of the caregivers knew their child’s/ward’s weight, only 50% had used it to determine the dose. Caregivers with previous experience (as caregivers) were most likely to have administered an inappropriate dose (P = 0.03). Physicians were the source most consulted (40%) by caregivers, followed by the product’s label (35%). Only 9% of the caregivers consulted a pharmacist for dosing recommendations. Conclusion: Nearly half of all the caregivers administered an incorrect acetaminophen dose, suggesting that there is a need for better caregiver education. Due to their accessibility at the point of sale of OTC medications and pharmacotherapy knowledge, pharmacists could have an active role in promoting the safe and effective use of acetaminophen.